2011
DOI: 10.1080/10632913.2011.546694
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Benefits of Music-Making as Professional Development for Music Teachers

Abstract: Although much has been written about professional development in general education and music education literature, little has addressed the benefits of music-making as meaningful professional development for music teachers. For music teachers, music-making and meanings of music-making have been connected with teachers' identity, well-being, beliefs, and effectiveness, as well as being a powerful pedagogical tool and a way to develop presence in teaching. Presence in teaching is linked with self-awareness, atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
1
38
0
3
Order By: Relevance
“…Music education scholars have given attention to developing teacher identity so as to prepare preservice teachers for their professional needs as educators (e.g., Ballantyne, Kerchner, & Aróstegui, 2012;Bouij, 2007;Garnett, 2014;Roberts, 2004). Others have advocated strengthening the musician identity (Bernard, 2005;Freer & Bennett, 2012;Pellegrino, 2011Pellegrino, , 2015. There are also scholars who have urged going beyond the binary focus on musician and teacher as constructs of music teacher identity (Dawe, 2007;Dolloff, 2007;Regelski, 2007).…”
Section: Music Teacher Identitymentioning
confidence: 99%
“…Music education scholars have given attention to developing teacher identity so as to prepare preservice teachers for their professional needs as educators (e.g., Ballantyne, Kerchner, & Aróstegui, 2012;Bouij, 2007;Garnett, 2014;Roberts, 2004). Others have advocated strengthening the musician identity (Bernard, 2005;Freer & Bennett, 2012;Pellegrino, 2011Pellegrino, , 2015. There are also scholars who have urged going beyond the binary focus on musician and teacher as constructs of music teacher identity (Dawe, 2007;Dolloff, 2007;Regelski, 2007).…”
Section: Music Teacher Identitymentioning
confidence: 99%
“…Supported teachers are offered diverse and numerous personal (Wu 2010;Zeng 2008) and professional development opportunities (Webb et al 2009;, which counteract job stress and teacher burnout (Ross et al 2012;Peng 2012;Wang 2011) and enhance societal support for teachers, overall . Pellegrino (2011) emphasized use of the aesthetic to enhance teacher professional development, while other studies highlight that teachers feel more valued by peers, evaluators, and students (Wu 2010;Peng 2012) when they feel efficacious in contributing to a harmonious societal future (Gao et al 2010). discusses teacher autonomy and support as two sides of the same coin.…”
Section: Teacher Autonomy and Supportmentioning
confidence: 99%
“…In addition, the enthusiasm and interests in music provoked Tin to take up challenges at work and explore his professional area. Therefore, the improvement of music knowledge and skills and the abilities of organising extra-curricular activity benefited their commitment to being a music teacher (Pellegrino, 2011). At the same time, music teaching was a good way to demonstrate their professional skills to others.…”
Section: Chapter 6 Conclusion and Recommendationsmentioning
confidence: 99%
“…Though conflicts may exist between performer and teacher identities (Mark, 1998;Scheib, 2003Scheib, , 2006Scheib et al, 2007;Wagoner, 2011), they may also be compatible in a unified music teacher identity (Pellegrino, 2011). In a recent study, Kokotsaki (2010) found that involvement in extra-curriculum music activities and music making outside school has both personal and professional benefits for music teachers.…”
Section: Performer/ Teacher Identitiesmentioning
confidence: 99%
See 1 more Smart Citation